“Bedside-to-Bench” Behavioral Outcomes in Animal Models of Pain: Beyond the Evaluation of Reflexes - Cobos, Enrique J (Bentham Science Publishers, 2013)
Despite the myriad promising new targets and candidate analgesics recently identified in preclinical pain studies, little translation to novel pain medications has been generated. The pain phenotype in humans involves complex behavioral alterations, including changes in daily living activities and psychological disturbances. These behavioral changes are not reflected by the outcome measures traditionally used in rodents for preclinical pain testing, which are based on reflexes evoked by sensory stimuli of different types (mechanical, thermal or chemical). These measures do not evaluate the impact of the pain experience on the global behavior or disability of the animals, and therefore only consider a limited aspect of the pain phenotype. The development of relevant new outcomes indicative of pain to increase the validity of animal models of pain has been increasingly pursued over the past few years. The aim has been to translate “bedside-to-bench” outcomes from the human pain phenotype to rodents, in order to complement traditional pain outcomes by providing a closer and more realistic measure of clinical pain in rodents. This review summarizes and discusses the most important nonstandard outcomes for pain assessment in preclinical studies. The advantages and drawbacks of these techniques are considered, and their potential impact on the validation of potential analgesics is evaluated.